Profile of Renal Transplant Patients Associated with Social Security or Continuous Cash Benefit and Labor Status - Colombo, Diva Marques de Quevedo (2022)
Chronic kidney disease consists of kidney damage and the progressive and irreversible loss of kidney function. Thus, when the kidneys are no longer able to maintain their functions, it is imperative that the individual access some benefit to facilitate treatment. Thus, the objective of this article was to analyze the social security or welfare and labor situation of the patient transplanted by a renal transplant unit. The research was carried out by means of a questionnaire with patients who attended the specialties outpatient clinic in October and November 2021. The project was approved by the Research Ethics Committee of the Faculdade de Medicina de São José do Rio Preto, Brazil, and the patients who agreed to participate in the research signed the informed consent form, complying with the ethical principles of the National Health Council and the Ethics Code of the Social Worker. For analysis purposes, after data collection, the variables age, gender and education made up the social profile of the interviewees (n = 20) with the distribution of the variables of social security status and work status, associated with the surveyed profile. In the social profile of the group studied, the female gender contrasted with the literature researched. The variation in the frequency detected of patients in social security or welfare assistance status confirms the impossibility of resuming conditions for professional exercise and, unfortunately, although small, it is an expressive portion of patients with no income or away from the labor market